Itinera Fiduciae. : Trust and Treuhand in Historical Perspective. - Helmholz, Richard (Comparative Studies in Continental and Anglo-American Legal History - Band 19., 2013)
Hauptbeschreibung A person may hold property for a variety of purposes. The most common situation is that he wants to use and enjoy it for his own benefit. But he may also have agreed to administer the property either for the benefit of someone else or to further some particular purpose. Thus, in a broad and untechnical sense of the word, he may hold it ""in trust"". This kind of arrangement has been resorted to for many different reasons, both legitimate and illegitimate. From very early on, European legal systems have been faced with the need to establish rules and, eventually, instit.